Stratigraphy of a Permian-Triassic fluvial-dominated succession in Southern Victoria Land (Antarctica): preliminary data - LIBERATO, GIOVANNI PIO; Gianluca Cornamusini; Matteo Perotti; Sonia Sandroni; Franco M. Talarico (Università degli studi, Roma La Sapienza. Dipartimento di scienze della terra, 2017)
Permian-Triassic deposits characterize largely Allan Hills, located at the edge of the East Antarctica Ice Plateau in the northern part of the Southern Victoria Land. Here, they show an extensive exposure of some hundreds meters thick siliciclastic continental succession of the Permian to Early Jurassic Beacon Supergroup. We present preliminary data of the stratigraphic-sedimentological features of these deposits focusing on the Permian-Triassic boundary (PTB). Fourteen stratigraphic sections on the Weller Coal Measures, Feather Sandstone Fm. (including the Fleming Member) and Lashly Formation, were logged and sampled across an area of ca. 25 square kilometers in the north-eastern sector of Allan Hills, obtaining a new geological map and a new stratigraphic frame. The studied portion of the succession is characterized by marked facies changes, particularly through the PTB, accompanied by remarkable changes in paleoflora, from Glossopteris- to Dicroidium dominated associations. The paleoenvironmental changes are marked by the transition from a wide floodplain with high-energy meandering streams developing coarse sandstone bars and wide marshes along the alluvial plain during the Permian, to braided sandy rivers lacking of significant vegetated apparatus during the Early Triassic, and then passing gradually to sandy-braided rivers with associated and increasing vegetated peats in the alluvial plain during the Middle Triassic. This evolutionary scenario emphasizes the climate deterioration linked with the PTB event determining a semiarid scenario during the Early Triassic, and then the progressive climate amelioration causing the reforestation and changing of the fluvial system during the Middle Triassic.